Psychoanalysis and ethics: the necessity of perspective - Black, David M. (New library of psychoanalysis, 2024)
Introduction -- The working of values in ethics and religion -- Jonathan Lear: heir to a different legacy -- Who founded Buddhism? Notes on the psychological action of religious objects -- Dante's Two Suns: the psychological sources of the Divine Comedy -- Dante, duality and the function of allegory -- Freud and idealization -- The transcendent in everyday life -- Religion as the affirmation of values -- Levinas's re-basing of religion.